MANAJEMEN PEMERINTAHAN DESA DALAM PROGRAM USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) DESA TANJUNG LEBAN KECAMATAN BANDAR LAKSAMANA KABUPATEN BENGKALIS TAHUN 2016-2017 - Muhammad Amir Muttakin; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Village government management is a process that consists of planning, organizing, financial management, coaching and development, decision making, management and supervision programs. Village government management in the UED-SP program to accelerate the level of community welfare development in Tanjung Leban Village.This study aims to: (1) To describe the Village Government Management in the Savings and Loans Village Economic Business Program (UED-SP) of Tanjung Leban Village. (2) To find out what factors become obstacles in the process of implementing Village Government Management in the Savings and Loans Village Economic Business Program (UED-SP) of Tanjung Leban Village. This research uses a qualitative research method with a descriptive approach, which can be interpreted as a problem solving process that is investigated by describing the state of the research subject based on the facts that appear during the research which is continued based on existing theories. Data analysis is performed by data reduction, data presentation, and drawing conclusions or verification. The subjects of this research are the Village Head, Chair of the Village Consultative Body (BPD), UED-SP manager, Village Assistant, Community Leaders, and United Blessed UED-SP Members.The results of this study indicate that the existence of Village Government Management in the Savings and Loans Village Economic Business Program (UED-SP), should be able to improve the arrears that occur in the UED-SP Berkah Bersatu, but in reality this arrears still occur due to several factors namely weak leadership village head, inadequate facilities, low mindset of the community, and Weak Supervision from the village government, this is an inhibiting factor in carrying out the process of village government management in the implementation of the UED-SP Berkah Bersatu